Analisis Dampak Intervensi Workshop Terhadap Kompetensi Manajerial Aktivis Organisasi Kemahasiswaan - Mujtahidah, Mujtahidah; Purnomo, Jeki; Rachman, Dian Anggraeni (Indo-MathEdu Intellectuals Journal, 2026)
Strengthening students’ managerial competencies has become a strategic necessity to enhance the effectiveness of student organizations and to prepare future leaders. This study aimed to analyze the impact of an experiential learning–based workshop intervention on the managerial competencies of student organization activists. A quantitative approach was employed using a pre-experimental one-group pretest–posttest design. The sample consisted of 30 core student organization board members selected through purposive sampling. Data were collected using a validated questionnaire measuring five managerial competency indicators: understanding of POAC (planning, organizing, actuating, controlling), organizational vision and mission, goal setting, organizational structure, and perceptions of the importance of organizational management. Data were analyzed using a paired sample t-test. The results indicated an increase in the mean score from 76.67 to 90.67, with a statistically significant difference (t(29)=2.97; p=0.006) and a moderate effect size (Cohen’s d=0.54). Four indicators showed significant improvement, while one indicator declined, which was interpreted as a critical reflective process following the intervention. These findings confirm that practice-based workshops are effective in enhancing students’ managerial competencies and should be sustainably integrated into student organization development programs.